PENELITIAN EKOLOGI NEPENTHES DI LABORATORIUM ALAM HUTAN GAMBUT SABANGAU KERENG BANGKIRAI KALIMANTAN TENGAH - Mansur, Muhammad (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Ecological studies on Nepenthes at Peat Swamps Forest Natural Laboratory, Kereng Bangkirai Sabangau, Central Kalimantan, was conducted on April to May, 2006. Survey method used for to known diversity of Nepenthes in study site and we made four small plots for population measurement. As the result, three species and one natural hybrid were founded, such as; Nepenthes gracilis, N. rafflesiana, N. ampullaria and N.xhookeriana. In study site, Nepenthes gracilis is wider distribution than other species, they can grow at open, rather shaded or shaded area and they have high density at open area. While, N. rafflesiana , N. ampullaria and N.xhooekeriana commonly foundedat rather shaded area or shaded area